A Checklist of the Herpetofauna of Nusa Kambangan Island, Central Java, Indonesia - Nia Kurniawan; Luhur Septiadi; Muhammad Fathoni; Ahmad Muammar Kadafi; Agung Pramana Warih Marhendra (Tropical Life Sciences Research, 2022)
An inventory of herpetofauna species from western part of Nusa Kambangan Island, Central Java, Indonesia, is presented. There are 43 herpetofauna species reported (16 amphibians and 27 reptiles). This study confirmed new distribution record and list some of threatened species. In light of the imminent human disturbances on Nusa Kambangan Island, a conservation plan is urgently needed.